1999
DOI: 10.1080/00288330.1999.9516876
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting settlement and early post‐settlement survival of the New Zealand abaloneHaliotis australis

Abstract: This paper describes studies on the settlement of the abalone Haliotis australis Gmelin. Ten-day-old H. australis larvae had a slower rate of settlement than 5-day-old larvae. A high proportion of veliger larvae had the ability to prolong the searching phase of settlement and delay metamorphosis, even over prepared settlement surfaces but radula development continued at a similar rate in both settled and swimming larvae. In any one batch of larvae settlement was slow and asynchronous and post-settlement surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 27 publications
1
16
0
1
Order By: Relevance
“…In the wild, the juvenile stages of abalone are closely associated with non-geniculate coralline algae (Roberts 2001). In laboratory experiments, coralline algae have been found to induce attachment and metamorphosis in all abalone species that have been tested, and there is evidence in some abalone species of settlement preferences for particular coralline species (Daume et al 1999;Moss 1999;Roberts 2001).…”
Section: Calcified Algae and Invertebrate Recruitment And Settlementmentioning
confidence: 96%
“…In the wild, the juvenile stages of abalone are closely associated with non-geniculate coralline algae (Roberts 2001). In laboratory experiments, coralline algae have been found to induce attachment and metamorphosis in all abalone species that have been tested, and there is evidence in some abalone species of settlement preferences for particular coralline species (Daume et al 1999;Moss 1999;Roberts 2001).…”
Section: Calcified Algae and Invertebrate Recruitment And Settlementmentioning
confidence: 96%
“…This behaviour has been commonly reported for invertebrates (Richmond, 1985;Gebauer et al, 1988;Pechenik et al, 1996;Moss, 1999;Chicharro and Chicharro, 2000) and for some reef fishes (Victor, 1986a,b;Sponaugle and Cowen, 1994;McCormick, 1999). Until now, delayed settlement has been viewed as a larval adaptation to expand the biogeographical range and to increase the chance of finding a suitable habitat in which to settle (Sponaugle and Cowen, 1994).…”
Section: Planktonic Period and Growth Ratementioning
confidence: 91%
“…We used GABA as a positive control in our study because it previously had been shown to induce larval settlement, attachment and/or metamorphosis in H. iris (Roberts 2001 australis (Moss 1999). However, the effective doses for these species vary between 0.5-10 µmol L -1 , implying species specificity.…”
Section: Discussionmentioning
confidence: 99%
“…The amino acid and neurotransmitter γ-amino butyric acid (GABA) consistently has been shown to induce larval attachment and metamorphosis of several abalone species (Morse 1990;Roberts & Nicholson 1997;Bryan & Qian 1998;Moss 1999). While a pure-form of GABA is unlikely to be an environmental cue (Kaspar & Mountfort 1995;Roberts & Watts 2010), abalone possess externally accessible chemosensory receptors which recognize GABA analogues and GABA-mimetic peptides extracted from crustose coralline algae (Morse et al 1979(Morse et al , 1980Trapido-Rosenthal & Morse 1986;Morse 1990).…”
Section: Introductionmentioning
confidence: 99%